Raised bed planting promotes grain number per spike in wheat grown after rice by improving spike differentiation and enhancing photosynthetic capacity - Xiang-bei DU; Min XI; Zhi WEI; Xiao-fei CHEN; Wen-ge WU; Ling-cong KONG (Journal of Integrative Agriculture, 2023)
The yield of wheat in wheat–rice rotation cropping systems in the Yangtze River Plain, China, is adversely impacted by waterlogging. A raised bed planting (RBP) pattern may reduce waterlogging and increase the wheat yield after rice cultivation by improving the grain number per spike. However, the physiological basis for grain formation under RBP conditions remains poorly understood. The present study was performed over two growing seasons (2018/2019 and 2019/2020) to examine the effects of the planting pattern (i.e., RBP and flat planting (FP)) on the floret and grain formation features and leaf photosynthetic source characteristics of wheat. The results indicated that implementation of the RBP pattern improved the soil–plant nitrogen (N) supply during floret development, which facilitated balanced floret development, resulting in a 9.5% increase in the number of fertile florets per spike. Moreover, the RBP pattern delayed wheat leaf senescence and increased the photosynthetic source capacity by 13.9%, which produced more assimilates for grain filling. Delayed leaf senescence was attributed to the resultant high leaf N content and enhanced antioxidant metabolism. Correspondingly, under RBP conditions, 7.6–8.6% more grains per spike were recorded, and the grain yield was ultimately enhanced by 10.4–12.7%. These results demonstrate that the improvement of the spike differentiation process and the enhancement of the leaf photosynthetic capacity were the main reasons for the increased grain number per spike of wheat under the RBP pattern, and additional improvements in this technique should be achievable through further investigation.